Ndeso’s Queer: The Spectators' Mirror of Rural Gay Narratives in the Film 'Pria' - Aptarina, Dhea (I-Pop: International Journal of Indonesian Popular Culture and Communication, 2022)
In societies with a culture of heteronormativity, including Indonesia, the gay community tends to be alienated and marginalized, especially in rural areas where social control is stringent and inherent. So, what is the life of a gay person in rural Indonesia? And how do gay audiences perceive content and narratives about this issue? This article reveals the reception of audiences from the gay community towards the film 'Pria,' which tells the story of the romance of a gay youth in a village in Indonesia. Using the spectatorship ethnography method, this study finds how film viewers reflect on the film's narrative and relate the characters' problems and experiences to their personal experiences and inner conflicts as gay people who also come from the village. This study is the first to investigate rural gay film viewing practices by gay viewers using a spectatorship ethnographic approach, making it a valuable reference for subsequent relevant studies and as a social reflection for society, especially in the cultural context of heteronormativity.